Radiological incidence of donor‐site incisional hernia and parastomal hernia after vertical rectus abdominus myocutaneous flap‐based reconstruction following colorectal surgery - Alethea Tang (Colorectal Disease, 2022)
AimThe vertical rectus abdominis myocutaneous (VRAM) flap is commonly used to reconstruct perineal defects for low rectal and anal cancer. The incidence of midline incisional hernias after VRAM reconstruction varies from 3.6% when detected clinically to 50% when detected radiologically. The aim of this study is to accurately determine the radiological incidence of donor-site incisional and parastomal hernia following VRAM reconstruction.MethodsRetrospective cohort study of patients undergoing colorectal surgery requiring VRAM reconstruction over 10 years. Data were collected on patient demographics, indication for surgery and surgical procedure including details of any hernia repair. Images from surveillance CTs were reviewed for presence and size of midline incisional and/or parastomal hernias. Parastomal hernias were classified based on the European Hernia Society (EHS) classification.Results173 patients were included in the analysis. The median age was 67 years (range 29 – 88 years) and median length of follow up was 49 months (IQR 24.3 – 71.0 months). The cumulative incidence of donor-site incisional hernia after VRAM at 1, 2 and 5 years was 15.1%, 25.4% and 29.1%. The cumulative incidence for PSH at 1, 2 and 5 years was 33.1%, 46.6% and 53.3% (95%CI 45.4% - 60.5%).ConclusionMost patients who develop donor-site incisional hernia and parastomal herniation following VRAM tend to do so within the first two years. Although the use of CT imaging improves the diagnosis of donor-site incisional and parastomal hernias, the clinical significance of this is unknown.